Hazards of the Market: The Continuity and Dissolution of Interorganizational Market Relationships - Бейкер, Уэйн; Фолкнер, Роберт; Фишер, Джин (Journal of Economic Sociology, 2010)
The suggested theory of the market as intra-timing process integrated the variety of different theoretical concepts. Basing on the event method analysis the authors investigate the breakup in organizational ties between the advertising agencies and their clients, influenced by the three market forces: competition, power relations and institutional enforcement. Informal rules of exchange institutionalized on the stage of formation of the advertising services market suggest “exclusive partnership” and loyalty. The research results show that in most cases the relationships between the advertising agencies and their clients are exclusive and remain constant for several years. However the competition, power relations and institutional enforcement give a certain impact on them encouraging or discouraging these rules. The institutional enforcement decreases the risk of breakup between the agency and the client. The most powerful agencies mobilize the resources in order to increase the stability of the ties while the most powerful clients have different behavior and use the resources to increase or decrease this stability. Competition is the weakest market force but its impact is clear and important. It always increases the risk of breakup in relations. The conclusion is that the market institutionalizes through the repeated imperfect exchange models as competition and change of norms, that regulate the market ties, destabilize the market relations.